2011
DOI: 10.1016/j.pscychresns.2010.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Poor decision-making by chronic marijuana users is associated with decreased functional responsiveness to negative consequences

Abstract: Chronic marijuana users (MJ Users) perform poorly on the Iowa Gambling Task (IGT), a complex decision-making task in which monetary wins and losses guide strategy development. This study sought to determine if the poor performance of MJ Users was related to differences in brain activity while evaluating wins and losses during the strategy development phase of the IGT. MJ Users (16) and Controls (16) performed a modified IGT in an MRI scanner. Performance was tracked and functional activity to early wins and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
134
3
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(146 citation statements)
references
References 52 publications
(73 reference statements)
6
134
3
3
Order By: Relevance
“…Studies of neural substrates indicate that cannabis users have decreased orbitofrontal and dorsolateral prefrontal cortical (dlPFC; Bolla et al, 2005) and increased cerebellum (Bolla et al, 2005;Vaidya et al, 2012) and ventromedial prefrontal cortex (vmPFC; Vaidya et al, 2012) recruitment during monetary decision making relative to controls. Furthermore, blunted responses to negative consequences (ie, loss) in prefrontal and anterior cingulate cortex (ACC) may subserve slower strategy development during monetary decision making in cannabis smokers (Wesley et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of neural substrates indicate that cannabis users have decreased orbitofrontal and dorsolateral prefrontal cortical (dlPFC; Bolla et al, 2005) and increased cerebellum (Bolla et al, 2005;Vaidya et al, 2012) and ventromedial prefrontal cortex (vmPFC; Vaidya et al, 2012) recruitment during monetary decision making relative to controls. Furthermore, blunted responses to negative consequences (ie, loss) in prefrontal and anterior cingulate cortex (ACC) may subserve slower strategy development during monetary decision making in cannabis smokers (Wesley et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although control performance was equivalent between the two groups, cannabis users displayed a significant deficit in awareness of commission errors, which was associated with decreased a activity in the anterior cingulate cortex and right insula, as well as in the bilateral inferior parietal and middle frontal regions [172]. [177] also reported a poorer performance on the IGT in active cannabis users. However, there were no differences during the initial strategy development phase, in which cannabis users showed reduced activity in response to losses in anterior cingulate cortex, ventromedial prefrontal cortex, precuneus, superior parietal lobe, occipital lobe and cerebellum compared to controls [177].…”
Section: Memorymentioning
confidence: 86%
“…Functional imaging studies comparing activation in both adult and adolescent chronic cannabis users with healthy controls during the performance of different cognitive tasks indicated that chronic cannabis users would use similar brain areas that engage these cognitive processes but often demonstrating an altered pattern of brain activity [151,152,157,[165][166][167][168][169][170][171][172][173][174][175][176][177]179,[181][182][183]. However, the level of performance of the cannabis users on the cognitive tasks employed was generally similar to that of controls [164,165,168,171,174,177], or at least within what may be considered a normal range of test performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations